Electrical Characterization of a Double-Layered Conductive Pattern with Different Crack Configurations for Durable E-Textiles - Koshi, Tomoya (Micromachines (Basel), 2020)
For the conductive patterns of electronic textiles (e-textiles), it is still challenging to maintain low electrical resistance, even under large or cyclic tensile deformation. This study investigated a double-layered pattern with different crack configurations as a possible solution. Patterns with single crack growth exhibit a low initial resistance and resistance change rate. In contrast, patterns with multiple crack growth maintain their conductivity under deformation, where electrical failure occurs in those with single crack growth. We considered that a double-layered structure could combine the electrical characteristics of patterns with single and multiple crack growths. In this study, each layer was theoretically designed to control the crack configuration. Then, meandering copper patterns, silver ink patterns, and their double layers were fabricated on textiles as patterns with single and multiple crack growths and double-layered patterns, respectively. Their resistance changes under the single (large) and cyclic tensile deformations were characterized. The results confirmed that the double-layered patterns maintained the lowest resistance at the high elongation rate and cycle. The resistance change rates of the meandering copper and silver ink patterns were constant, and changed monotonically against the elongation rate/cycle, respectively. In contrast, the change rate of the double-layered patterns varied considerably when electrical failure occurred in the copper layer. The change rate after the failure was much higher than that before the failure, and on the same order as that of the silver ink patterns.